Stability of an oral ranitidine suspension (15 mg/ml). Issue 1 (14th July 2012) - Petit-Jean, Emilie; Perello, Laurent; Hernandez, Céline; Dory, Anne-Cécile Gairard; Gourieux, Bénédicte; Ubeaud-Sequier, Geneviève
Abstract : Purpose: The aim of this study was to evaluate the microbiological and physicochemical stability of 15 mg/ml ranitidine hydrochloride suspension. Methods: 15 mg/ml ranitidine hydrochloride suspensions were prepared in commercial vehicle (ORA-BLEND). Suspensions were kept for 90 days at 4 °C and 25 °C. The microbiological stability was assessed by microbial enumeration tests and specific search for Escherichia coli The physical stability was assessed by colour change, pH and chromatogram peaks. Ranitidine was assayed using high-performance liquid chromatography. Each series of three batches at each storage condition was combined into one representative exponential curve for the evolution of degradation of ranitidine suspension. Stability was defined as a remaining concentration of at least 95 % of the initial concentration (ie, 5% degradation). Results: Culture of the different suspension samples resulted in no bacterial or fungal growth. Specific search for E coli was negative. There was colour change for each batch. No change from the initial pH (4·2) occurred in samples stored at 4°C but, for samples stored at 25°C, the pH increased from 4·2 to 4·9. Unidentified peaks corresponding to degradation products appeared on the chromatogram at day 30 for suspensions stored at 25°C and at day 60 for suspensions stored at 4°C. Conclusions: Ranitidine hydrochloride suspension in amber glass was stable for up to 27 days when stored at 4°C and up to 5 days at 25°C. It is recommended that nurses should allow ranitidine suspension to reach room temperature before use and administration to patients.